The Antibacterial Potential of Ethyl Acetate Fraction from Plectranthus amboinicus Leaves and Identification of Active Compounds Using LC-MS - Martha, Rahma Diyan; Safitri, Yunita Diyah; Lestari, Nasa Bela Dwi; Danar, Danar; Parbuntari, Hesty; Maida, Margarita Claudya; Muadifah, Afidatul; Huda, Choirul (Universitas PGRI Madiun, 2024)
The Indian Borage plant (Plectranthus amboinicus) is a traditional medicinal ingredient in Indonesia, containing flavonoids, alkaloids, polyphenols, saponins, and essential oils. Therefore, this study aimed to determine the antibacterial activity of P. amboinicus leaves ethyl acetate fraction using the disc diffusion method and identify the composition with LC-MS. The antibacterial activity test was conducted with concentration variations of 15%, 20%, and 25% with Chloramphenicol 500 mg and 5% DMSO as a positive and negative control, respectively. The results showed that the ethyl acetate fraction at a concentration of 20% had the largest inhibition zone diameter, with an average of 30 mm. The LC-MS results identified 115 compounds, and the highest concentration values were found in kaempferol 3-(6”-caffeoylglucoside) and kaempferol 3-glucosyl-(1→2) galactosyl-(1→2)-glucoside, with a composition of 3.26109% and 3.26141%, respectively.